Post-acne scars: what a specialist should know about scarring of the skin. A review - Mari M. Karapetyan; Evgeniya V. Dvoriankova; Irina M. Korsunskaya (Consilium Medicum)
Acne is a relatively common dermatological problem in adolescents and adults. Acne may resolve, leaving post-inflammatory erythema, depigmentation, and scarring. Scars often cause low self-esteem, depression, and anxiety. Skin damage caused by acne triggers a cascade of reactions aimed at wound healing, including three stages: inflammation, formation of granulation tissue, and matrix remodeling. An imbalance of matrix metalloproteases and their tissue inhibitors at the last stage leads to atrophic or hypertrophic scars. The atrophic scars are characterized by the loss of collagen during wound healing: 80–90% of patients with post-acne scarring develop atrophic scars, which are divided into three types. The most common are "axe scars," followed by rolling scars, and "freight car" scars are less common. However, it should be noted that all three types of scars can form in the same subject. The formation of hypertrophic and keloid scars is associated with excessive collagen deposition due to decreased collagenase activity. These types of scars mainly occur in people with darker skin color and are predominantly localized on the trunk. The most effective way to control post-acne scars is through prevention with proper acne treatment. A wide range of tools is used to treat existing scars, from chemical peels to laser correction, but combined methods show better results.